2012
DOI: 10.1021/jp301528q
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Spectroscopy, and Structure of Cyanoformyl Chloride and Cyanoformyl Bromide, XC(O)CN

Abstract: Cyanoformyl chloride and cyanoformyl bromide, XC(O)CN (X = Cl and Br), have been investigated in the gas phase by UV photoelectron and mid-infrared spectroscopies. The ground-state geometries of the neutral molecules have been obtained from quantum-chemical calculations at the B3LYP and CCSD(T) levels using the aug-cc-pVTZ basis set. The individual spectroscopies provide a detailed investigation into the vibrational and electronic character of the molecules and are supported by quantum-chemical calculations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is well-known that the detailed analysis of band contours in infrared spectra can provide valuable information regarding the gas-phase structure of rotamers. The experimentally observed band contours for CF 3 CH 2 SNO and CH 3 CH 2 SNO are also listed in Tables and . Calculated rotational constants (cm –1 ) and molecular parameters, together with the estimated separation between P and R branches [Δν(PR) values, in cm –1 ] as obtained following the classical method of Seth-Paul, are collected in Table .…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that the detailed analysis of band contours in infrared spectra can provide valuable information regarding the gas-phase structure of rotamers. The experimentally observed band contours for CF 3 CH 2 SNO and CH 3 CH 2 SNO are also listed in Tables and . Calculated rotational constants (cm –1 ) and molecular parameters, together with the estimated separation between P and R branches [Δν(PR) values, in cm –1 ] as obtained following the classical method of Seth-Paul, are collected in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The cyanoformaldehyde “motif” appears in many related molecules where the carbonyl hydrogen is substituted for another atom or functional group. For example, cyanoformyl chlorides, acetyl cyanide, or carbonyl cyanide have all been studied as well as its sulfur-bearing analogue and isomers …”
Section: Introductionmentioning
confidence: 99%
“…The cyanoformaldehyde "motif" appears in many related molecules where the carbonyl hydrogen is substituted for another atom or functional group. For example, cyanoformyl chlorides, 6 acetyl cyanide, 7 or carbonyl cyanide 8 have all been studied as well as its sulfur-bearing analogue and isomers. 9 To the best of our knowledge, the whole family of cyanoformaldehyde isomers has not been studied systematically in any theoretical or experimental work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on this molecular transformation, cyanoformamides could be formed via cyanoformyl chloride from the commercially available trichloroacetonitrile ( 1 ) by the B 12 derivative as a redox mediator at room temperature in the air using the electrochemical method. The cyanoformyl chloride has an impact on synthetic organic chemistry to transform various fine chemicals, and its spectroscopic or theoretical analysis has been investigated due to the unique chemical properties . Nevertheless, only a few studies have reported generating cyanoformyl chloride that requires very harsh reaction conditions by thermolysis or pyrolysis …”
mentioning
confidence: 99%